Incidence And Risk Factors Of Maternal And Fetal Outcomes Among Patients Of Placenta Previa With And Without Placenta Accreta - Samina Naseem Khattak; Umbreen Akram; Erum Pervaiz; Maria Anayat; Tahir Ahmad Munir; Naheed Akhter; Athar Ahmad Jan (Journal of Bahria University Medical and Dental College)
Objective: The aim of the study was to evaluate maternal and fetal outcomes among patients of placenta previa (PP) with and without placenta accreta (PA). Methodology: All patients who underwent cesarean section for PP and PA were analyzed retrospectively at a tertiary care Combined Military Hospital Kharian, Pakistan, from February 2015 to March 2018. Maternal and neonatal data were obtained from medical records and the hospital database system. Results: PA was found in 37 patients from 111 patients of PP and 74 were without PA with the rate of approximately 2/1000 and 4/1000 respectively were included in the study. The mean age was 31.16±2.65 (range 22–37) years, mean gravidity of 3.69 ±1.40 (range 1 - 9), mean parity 2.57±1.01 (range 1–5), mean number of cesarean sections 2.10±0.66, (range 1-3) and a mean gestational age at the time of cesarean section was 35.65±2.46 (range 28–41) weeks. The maternal risk factors revealed marked differences between placenta previa with accreta and without accrete. The mean intraoperative blood loss in PA was 3,000ml, with a loss of 2,000ml occurring in 60%, and 3,000 ml in 21% of the PA cases. The mean pRBC transfusion was 4 units, while 17% received 6 units. Fetal growth restriction was not seen. A total of 12 neonates were admitted in NICU, with 03 neonatal deaths. There was no maternal death. Neonates born to women with placenta accreta had significantly lower birth weight, Apgar scores at 1 min and 12% required admission to NICU with 3 neonatal deaths. Conclusion: The advanced maternal age, past cesarean or uterine surgery, high parity as well as multiple gravidity were the risk factors for adverse fetal and maternal outcomes.